2020
DOI: 10.2298/vsp181108192c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Custodiol® and modified St. Thomas cardioplegia for myocardial protection in coronary artery bypass grafting

Abstract: Background/Aim. Custodiol is a hyperpolarizing cardioplegic solution which has been used in our national cardiac surgical practice exclusively for the heart transplant surgery. Owing to its numerous advantages over the standard depolarizing solutions, Custodiol became cardioplegia of choice for all other cardiac surgical procedures in many cardiosurgical centers. This study evaluates myocardial protection of Custodiol compared to modified St. Thomas cardioplegia in coronary artery bypass surgery. Methods. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This article updates the previous meta-analysis Reynolds et al 2020 (26), with four added RCTs [ 16 , 17 , 23 , 25 ]. Our findings were consistent with the previous ones to a large extent.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This article updates the previous meta-analysis Reynolds et al 2020 (26), with four added RCTs [ 16 , 17 , 23 , 25 ]. Our findings were consistent with the previous ones to a large extent.…”
Section: Discussionsupporting
confidence: 63%
“…The mixture was delivered through an antegrade route at a pressure of 80–100 mmHg, and was repeated every 30–45 min. Before myocardial perfusion, another warm blood retrograde dose was administered Cvetković et al [ 17 ] Serbia 104 patients (54 for HTK, and 50 for MDC) The study included adult patients undergoing CABG, having at least two angiographic graftable target vessels (> 2.0 mm in diameter, with ≥ 70% stenosis), LVEF ≥ 30%, and normal valves. Patients > 80 years, having MI within a month of the operation, reoperation, medical emergency off-pump CABG, ongoing myocardial ischemia, pericarditis, coronary endarterectomy, LV surgical restoration, left main stenosis > 50%, or serum creatinine > 200 µmol/L were excluded 20 mL/kg of the solution were administered over 6–8 min, at 4–8 °C, through an antegrade route Crystalloid An initial one liter of St.Thomas solution was administered, over 3–5 min, at 4–8 °C, through an antegrade route.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak values of all enzymes were 6h after surgery. 11 Similarly, a meta-analysis performed by 16 (who studied the effects of blood cardioplegia versus crystalloid cardioplegia during cardiac surgery of pediatric) reported that cardiac troponin I level postoperatively was not significantly different between two groups with no evidence of improvement in myocardial injury for either groups .Also study comparing three groups ( custodiol group , st.thomas cardioplegia group and blood cardioplegia solution) during pediatric cardiac surgery and evaluate protective effects of three groups on the myocardial of the heart and found that CK-MB and troponin t levels were not statistically significantly different among the three groups with no superiority for HTK 7 .…”
Section: Discussionmentioning
confidence: 99%